SISTEM PENDUKUNG KEPUTUSAN SELEKSI TENAGA KERJA UNTUK SECURITY SERVICE MENGGUNAKAN METODE ARAS - Tetty Rosmaria Sitompul; Nelly Astuti Hasibuan (STMIK Budi Darma, 2018)
PT. ISS INDONESIA is a company that already has employees, which is very big. With seven branches spread across Indonesia, PT. ISS INDONESIA has more than 500 workers. Recruitment will continue as the opening of supermarkets or PT. ISS INDONESIA requires additional employees to develop or fill in empty formations. Subjects in this study are the application of decision support systems used to assist employee selection process in accordance with the criteria set by the management PT. ISS INDONESIA. System design with modified waterfall process model includes the definition of requirements required by the user in order to design the system for process modeling, data modeling, and user interface. In this research, it is expected to produce Decision Support Candidate Selection Software System With ARAS Method that can be used to manage employee candidate data and computerized criteria ranging from weighting, calculation of dominance value, arithmetic preference, calculation of index value and ARAS calculation.